Patient-reported outcome measures and clinical outcomes following peri-implant vestibuloplasty with a free gingival graft versus xenogeneic collagen matrix: a comparative prospective clinical study - Xiaojiao Fu; Ying Wang; Bo Chen; Jiehua Tian; Ye Lin; Yu Zhang (International Journal of Implant Dentistry, 2021)
Abstract Background The objective of this study was to compare patient-reported outcome measures (PROMs) and clinical outcomes after augmentation with xenogeneic collagen matrix (XCM) or free gingival graft (FGG) during different postoperative phases. Methods Forty-two patients (21 per group) with keratinized mucosa width (KMW) of < 2 mm at buccal implant sites in the posterior mandible were enrolled. All underwent vestibuloplasty and were allocated to either FGG (control) or XCM (test) group. Intraoperative morbidity of pain, stress, nausea, tolerance to time, and acceptance of surgery were evaluated immediately after surgery. The severity and duration of subjective pain, swelling, and bleeding were compared within a 2-week postoperative period. The willingness to retreat and satisfaction were assessed at 6 months. All PROMs were obtained using questionnaires and visual analog scales. The buccal KMW and other peri-implant parameters were also evaluated. Results No significant between-group differences were observed in PROMs immediately after surgery, except acceptance of surgery (0, 0–30.0 vs. 30, 0–50.0, p = 0.025). At 2 weeks, pain severity (46.7 ± 25.9 vs 61.9 ± 20.2, p = 0.040) and duration (5.52 ± 3.57 vs 8.48 ± 2.80, p = 0.005) were significantly lower in the test group, and pain perception during speaking and chewing was significantly higher for FGG, with no significant between-group differences in swelling and bleeding. At 6 months, the test group showed a higher willingness to retreat (76% vs 43%, p = 0.021); however, satisfaction with treatment outcomes was similar in both groups. At 6 months, the gain of KMW was significantly higher in FGG than in XCM (XCM: 1.57 ± 1.69 mm, FGG: 2.68 ± 1.80 mm, p = 0.003). Other peri-implant parameters did not show significant differences. Conclusions Within the limitation of the present nonrandomized study, XCM demonstrated more positive PROMs than FGG during different postoperative phases, mainly for less pain perception during the early healing stage, but was inferior to FGG in terms of gain of KMW. For KMW augmentation in the posterior mandible, XCM may be indicated when patients can bear little pain. Clinical trial registration ChiCTR1900022575 , date of registration: 17/4/2019, retrospectively registered,